Hybric Learning Challenges - Manley Baeza, Maureen Cristina (2023)
Education has always been considered a fundamental element for the socioeconomic development of countries. For this reason, research has been carried out, developed approaches, paradigms and within which hybrid education is found. This is understood as a combination of face-to-face and virtual classes, where ICTs play a predominant role in pedagogical mediation for this education model. This education model also entails a series of challenges for the educational institution, teachers and students. The foregoing because it requires having infrastructure, resources and technological equipment, connectivity, skills on the part of teachers, among others that many institutions and students lack. Therefore, there are many challenges that must be faced and that must be analyzed and considered as an essential part to make this teaching modality effective. In the present work, a small outline of some topics related to hybrid education will be made, such as Incidence of ICTs and technological tools in hybrid education and Synchronous and asynchronous communication in hybrid education, since they are considered fundamental elements in this type of education. teaching and learning. The foregoing because they are elements that in one way or another are not only closely related to the subject, but also have an influence on the success or failure of hybrid education.